Inclusive Education in Bilingual and Plurilingual Programs - (:unkn) unknown (My University, 2024)
This chapter examines the inclusion of students with Additional Educational Needs (AEN) in language education opportunities for in English-medium, Irish-medium and Gaeltacht schools in Ireland. The commitment to inclusive education as demonstrated by policy and in law is analysed, and the extent to which implementation aligns with this commitment examined. This chapter demonstrates that there are ideological, policy-related and resource-related challenges to inclusion in language education in rhe Irish context, and that these challenges are shared with other bilingual contexts. There has, however, been substantial progress towards inclusion in Irish-medium and Gaeltacht schools in recent years, driven largely by Irish-medium and Gaeltacht teachers, researchers and Irish-speaking communities. With regard to methodology, this chapter employs a narrative review of the literature which is not systematic in nature. A narrative review was chosen due to the broad focus of this chapter and the need for a variety of types of sources, which would not be well-captured in a single search. The research analysed pertains to both primary and post-primary schools, and draws on literature from both the Republic of Ireland and Northern Ireland, as well as international literature. Literature in both Irish and English was analysed. Given the relatively small literature base in the Irish context, grey literature was included and weight was not placed on impact scores or number of citations. Searches were conducted in Google Scholar pertaining to inclusive education in all bilingual and immersion contexts, in the Irish context generally, as well as in the Irish-medium context. As an example, in order to find studies pertaining to inclusive education in the Irish context, the keywords “inclusive education” “special education” “SEN” “special educational needs” were used in combination with the terms “Irish-medium education” “gaelscoileanna” “Gaeltacht” and “Gaeltacht schools”. The references of these papers were also examined to identify any additional sources, and the Cited By function on Google Scholar was used to identify more recent studies which had cited the papers. The aim of this search was to identify studies to date which have examined inclusive and special education in the Irish context. In addition, the key policy relating to Irish-medium education Polasaí don Oideachas Gaeltachta [Policy for Gaeltacht Education] 2017-2022 (Government of Ireland, 2007) was analysed, as was the key legislation underpinning inclusive education in Ireland, the Education for Persons with Special Educational Needs (EPSEN) Act (2004). In addition, annual reports of the National Council for Special Education (NCSE) were analysed. To provide context for the rest of the chapter, this chapter begins by discussing definitions of inclusive education in the literature and introducing the Irish context.
Inclusive and Special Education in English-Medium, Irish-Medium, and Gaeltacht Schools: Policy and Ideology of a Fragmented System
PUBLISHED
Keywords: Inclusive Education; Irish; Irish exemptions; Immersion education